Training Manual on Bundled Climate Smart Agriculture, Climate Information Services and One-Health Technologies for Priority Value Chains - Yeboah, Stephen; Martey, Francisca; Clottey, Victor; Damba, Osman Tahidu; Adomako, Joseph; Amankwaa-Yeboah, Patricia; Frimpong-Annin, Kofi; Wadie, Blankson Amoabeng; Haleegoah, Joyce; Badu-Brempong, Mavis; Dalaa, Mustapha Alasan; Obeng, Faustina; et al. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The manual is an addendum to the prioritized and bundled Climate Smart Agriculture (CSA) and Climate Information Services Innovations that is One Health Sensitive. The manual is designed as an extension and training tool for trainers of trainees (TOT) and extension agents to support smallholder farmers most especially stakeholders in AICCRA intervention communities. Users will find the manual very useful and it is hoped that Agriculture Extension Agents (AEAs), farmers, students, and other end users will apply the modules to increase crop production in the target agroecologies. Specifically, the manual provides climate information services, climate smart agriculture innovations and one health intervention that have been prioritized along maize, cowpea, yam, sweetpotato and tomato value chains.